2020
DOI: 10.1002/iub.2357
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA‐9‐5p and microRNA‐128‐3p can inhibit ischemic stroke‐related cell death in vitro and in vivo

Abstract: Ischemic stroke is the major form of stroke and is accentuated by multiple comorbidities. It has been previously shown that different microRNAs (miRNAs) regulate separate aspects of ischemic stroke. Differential miRNA expression analysis in cerebrospinal fluid of stroke patients had revealed upregulation of miR-124-3p, miR-9-3p, miR-9-5p, and miR-128-3p. However, whether the overexpression is correlative or causative was not known. Here, using an in vitro oxygen-glucose deprivation/reoxygenation (OGD/R) neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
15
2
Order By: Relevance
“…We also observed that upregulation of miR-124 by ago-miR-124 protected neurons against apoptotic cell death and improved behavioral performance by decreasing DAPK1 and apoptosisrelated proteins, including caspase-3 and cleaved caspase-3. A previous report by Yan et al (2020) demonstrated that miR-124 expression was significantly increased after OGD (Yan et al, 2020). This differs from our findings, possibly due to the use of primary cultured neurons vs. the N2a cells used by Yan et al (2020).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also observed that upregulation of miR-124 by ago-miR-124 protected neurons against apoptotic cell death and improved behavioral performance by decreasing DAPK1 and apoptosisrelated proteins, including caspase-3 and cleaved caspase-3. A previous report by Yan et al (2020) demonstrated that miR-124 expression was significantly increased after OGD (Yan et al, 2020). This differs from our findings, possibly due to the use of primary cultured neurons vs. the N2a cells used by Yan et al (2020).…”
Section: Discussioncontrasting
confidence: 99%
“…A previous report by Yan et al (2020) demonstrated that miR-124 expression was significantly increased after OGD (Yan et al, 2020). This differs from our findings, possibly due to the use of primary cultured neurons vs. the N2a cells used by Yan et al (2020). Although the specific reason for the difference is unclear, our results were confirmed by the PIT-stroke model.…”
Section: Discussioncontrasting
confidence: 95%
“…Data were expressed as mean AE standard deviation, and analyzed using one-way ANOVA, followed by Tukey's multiple comparisons test, **p < 0.01. fluid of stroke patients, and repression of miR-128 can reduce cell death and infarct volume. 22 miR-128 expression in patients with acute ischemic stroke is elevated with the aggravation of this disease. 23 Neurons are first directly affected by insufficient blood flow due to their inherent high energy requirements.…”
Section: Discussionmentioning
confidence: 97%
“… 39 Recent studies have revealed that miR-9-3p was significantly upregulated in cerebrospinal fluid of stroke patients compared with that of normal subjects. 12 , 14 , 40 However, the role and specific mechanisms of miR-375 in I/R-induced injury in the brain remains unclear. In agreement with a previous study finding that miR-9-3p was significantly elevated in the cerebrospinal fluid of stroke patients, 40 our study found that miR-9-3p was significantly upregulated in the I/R model, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 14 , 40 However, the role and specific mechanisms of miR-375 in I/R-induced injury in the brain remains unclear. In agreement with a previous study finding that miR-9-3p was significantly elevated in the cerebrospinal fluid of stroke patients, 40 our study found that miR-9-3p was significantly upregulated in the I/R model, both in vitro and in vivo. Studies on embryonic stem cells imply that miR-9 plays a key role in neural fate determination in mammalian brain development.…”
Section: Discussionmentioning
confidence: 99%